PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PRODUK SMARTPHONE XIAOMI (STUDI KASUS DI JAKARTA BARAT) - Hermanto Liu (Universitas Bunda Mulia, 2019)
ABSTRACTThe existence of a decrease in product sales Smartphone Xiaomi significant gains from the year 2015-2016,due to Intense competition in the telecommunications business are on the rise. This research aims to knowthe influence of the brand image and product quality against the interest of the consumer to buy the productin the region of Xiaomi Smartphone West Jakarta taken Samples as many 100 respondents. The method used is the quantitative methods based on the results of interviews and questionnaires for testing instrument using the test validity, and reliability. Data analysis techniques using multiple linear regression due to variables that are used more than two variables, with the t-test and F-test. The research results showed that the t-test with a brand image partially effect significantly to interest consumers buy Smartphone Xiaomi. While the quality of the product partially do not affect significantly to interest consumers buy Smartphone Xiaomi. F test results show that simultaneously the brand image and product quality significantly to influential interests buy consumer products Smartphone Xiaomi. And brand image is the most influential variables are dominant against the interest of the consumer to buy the product of Xiaomi Smartphone onthe quality of the product. Keywords: Brand Image, Product Quality and Interest To Buy.